PHD2 Deficiency in Endothelial Cells and Hematopoietic Cells Induces Obliterative Vascular Remodeling and Severe Pulmonary Arterial Hypertension in Mice and Humans through HIF-2α - Dai, Zhiyu (Circulation, 2016)
BACKGROUND: Vascular occlusion and complex plexiform lesions are hallmarks of the pathology of severe pulmonary arterial hypertension (PAH) in patients. However, mechanisms of obliterative vascular remodeling remain elusive and hence current therapies have not targeted the fundamental disease modifying mechanisms and result in only modest improvement in morbidity and mortality. METHODS AND RESULTS: Mice with Tie2Cre-mediated disruption of Egln1 (encoding prolyl-4 hydroxylase 2, PHD2) (Egln1(Tie2)) in endothelial cells (ECs) and hematopoietic cells exhibited spontaneous severe PAH with extensive pulmonary vascular remodeling including vascular occlusion and plexiform-like lesions resembling the hallmarks of the pathology of clinical PAH. As seen in idiopathic PAH patients, Egln1(Tie2) mice exhibited unprecedented right ventricular hypertrophy and failure and progressive mortality. Consistently, PHD2 expression was diminished in lung ECs of obliterated pulmonary vessels in idiopathic PAH patients. Genetic deletions of both Egln1 and Hif1a or Egln1 and Hif2a identified hypoxia-inducible factor-2α (HIF-2α) as the critical mediator of severe PAH seen in Egln1(Tie2) mice. We also observed altered expression of many PH-causing genes in Egln1(Tie2) lungs which was also normalized in Egln1(Tie2)/Hif2a(Tie2) lungs. PHD2-deficient ECs promoted smooth muscle cell proliferation in part through HIF-2α-activated CXCL12 expression. Genetic deletion of Cxcl12 attenuated PAH in Egln1(Tie2) mice. CONCLUSIONS: These studies defined an unexpected role of PHD2 deficiency in the mechanisms of severe PAH and identified the first genetically modified mouse model with obliterative vascular remodeling and pathophysiology recapitulating clinical PAH. Thus, targeting PHD2/HIF-2α signaling is a promising strategy to reverse vascular remodeling for treatment of severe PAH.